Thiết kế và cài đặt giao diện đồ họa trợ giúp học sinh vẽ hình phục vụ học sinh giải bài toán chứng minh hình học phẳng - Thủy, Nguyễn Thanh; Đức, Nguyễn Hữu (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall investigate some aspects on the design and implementation of a graphic interface for supporting figure construction and proof setting. This subsystem  is designed as a microworld in the “What You Get Is What You See” principle. The most interesting features here are macro construction and  possibility of defining  a trajectory of a point when another objects is moved. Besides the interface allows also students to manipulate directly geometry objects that help them to discover useful properties in the figure. The subsystem is implemented in Borland C for Window version 3.1.